2021
DOI: 10.1002/cbic.202100192
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a Thermostable Biocatalyst for the Synthesis of 2‐O‐Glucosylglycerol

Abstract: 2‐O‐Glucosylglycerol is accumulated by various bacteria and plants in response to environmental stress. It is widely applied as a bioactive moisturising ingredient in skin care products, for which it is manufactured via enzymatic glucosylation of glycerol by the sucrose phosphorylase from Leuconostoc mesenteroides. This industrial process is operated at room temperature due to the mediocre stability of the biocatalyst, often leading to microbial contamination. The highly thermostable sucrose phosphorylase from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The 2-GG selectivity of the enzymes was between 80 and 85%. Overall, therefore, when assessed as whole cell catalyst for 2-GG production, the P134Q variant of BaSucP served the purpose of a selective and stable catalyst, thus strongly supporting the antecedent molecular engineering of the enzyme (Franceus et al 2021).…”
Section: Enzyme Selectionmentioning
confidence: 64%
See 2 more Smart Citations
“…The 2-GG selectivity of the enzymes was between 80 and 85%. Overall, therefore, when assessed as whole cell catalyst for 2-GG production, the P134Q variant of BaSucP served the purpose of a selective and stable catalyst, thus strongly supporting the antecedent molecular engineering of the enzyme (Franceus et al 2021).…”
Section: Enzyme Selectionmentioning
confidence: 64%
“…The BaSucP is more stable but less regioselective (~65%) than LmSucP. The BaSucP_P134Q variant was developed (Franceus et al 2021) to confer regioselectivity (83±3%) to the stable enzyme. Measured in cell-free extract (N = 2) for 30 min using~0.3 M sucrose and~1.8 M glycerol, the specific activity at 30°C of LmSucP and BaSucP_P134Q was 792±86 and 794±57 U g −1 cell wet weight, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The used enzymes are stereospecific and show high regioselectivity on glycerol (>80% 2-GG). 14 The glycerol substrate is applied in excess (up to six-fold) for two reasons. First, sucrose conversion is driven to completion.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonging the catalysis time could reduce impurity I, but impurity III increased simultaneously, with more time cost generally disfavored in industrialization 35. With the intention of controlling impurities, a semi-rational design strategy of the enzyme was further applied 36. The structures of impurities I and III indicated that their formation was attributed to the regioselectivity and promiscuity of SPase 29,33.…”
mentioning
confidence: 99%